(3JMQjQ cJGH CUhd GdgfOSI hGdMSGH dChbdjOSs - (3eMeO Hf eMeO Hf GdMSf, CHh LYaQ, fUjQ GdOjf GdWhSj , J (B672 (3g` s; (3GbdjOSs
(3ChdgG (B:s
(3hHYO , adeG aQZJ ef JMQjQ (B"(3GdeLSWi(B" (3QCjJ Cf CMQQ cJGH (B"(3CUhd GdgfOSI hGdMSGH(B" (3GdefShH Edi ChbdjOS s
(3BNQgG (B:s
(3hEPG hab Gddg ai JMQjQ gPG GdcJGH MSH eG bUOJg adCNJe s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B924 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA QjGVjGJ (B- (3bSe (B3 - (3U (B25 s
(3eUOQ GbJfGA GdCUd (B:s
(3HdOjI GdEScfOQjI (B(5198 (3M(B) s
Keywords: (3GdQjGVjGJs